MURABAHAH ANTARA LAWFULL DAN DOUBTHFULL (Analisis Produk Murabahah di KSU Sejahtera UMP) - Ida Nurlaeli; Mintaraga Eman Surya (At-Taqaddum, 2015)
In the discussion about product Shari'ah financial institutions, Murabaha product into a product that is always in doubt syar'i. Then the article the results of this study aims to gain an overview of how the application of Murabaha product in KSU Sejahtera UMP. Is it in accordance with the provisions of Shari'ah in terms of both technical/hakikatnya. Artikel axiological and in terms of the results of this study using a qualitative approach. While data collection techniques using interviews, observation, documentation. Analysis of the data using descriptive analysis through three procedures of data reduction, data display and conclusion. From the data obtained and analyzed qualitatively. The results showed that technically/axiological, Murabaha product implementation at KSU Sejahtera Sharai UMP has met the criteria. For example KSU Sejahtera UMP has positioned the institution as a seller, though not directly provide these items in place but KSU Welfare has established cooperation with several providers of goods required by customers.